Systematic Literature Review: Satu Dekade Riset Akuntansi Posmodern di Indonesia - Arliena Hafni, Diska (UMSurabaya Publishing, 2025)
This study aims to analyze the results of postmodern accounting research for 10 years (2014-2024) in the form of journal articles based on topic categories, research objectives, figures of thought used as references and research data. The research method uses a qualitative approach, article data collection is taken from SINTA indexed journal and systematic literature review is used to analyze the data. The results showed that 1) Research topics in postmodern accounting research are mostly dominated by Islamic accounting topics (30%), then management accounting topics (20%), accounting theory (20%), accounting fraud topics (10%), and other topics by 5% each; (2) 80% of postmodern accounting research aims to deconstruct meaning, 10% analyze hegemony in accounting and 5% each analyze narrative (metanarrative) and analyze social relations and power in accounting; (3) Most accounting research with the postmodern paradigm refers to the thinking of Jacques Derrida (27%), 9% each refers to the thinking of Jean-Francois Lyotard and Paul Michel Foucault. The remaining 5% of research each refers to the thoughts of other figures; (4) 65% of postmodern accounting research uses research data in the form of documents (literature studies), 15% use interview techniques, 5% observation and 15% combine interview, observation and documentation techniques.